IMPLEMENTATION OF CASHLESS POLICY STRATEGIES TO MINIMIZE FRAUD IN THE GOVERNMENT SECTOR: SYSTEMIC REVIEW - Ridwan Ridwan; Syukriy Abdullah; Fifi Yusmita (UNIB Press, 2022)
Cashless financial transactions require information technology to transfer funds for the payment of needs, expenditures, and local government revenues. The potential that causes fraud and corruption can be minimized with non-cash transactions because financial transactions are more transparent. This study aims to identify fraud prevention strategies by implementing a cashless policy. This research was conducted systematically through an article search engine using the keywords